2019
DOI: 10.32601/ejal.651391
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Task-based Language Assessment into Young Learner Classrooms

Abstract: Task-based language assessment (TBLA) is a way of providing information about language learning in authentic settings. Not only does it present language learners with a meaningful and embedded context of assessment but also promotes communication in the target language. Within the framework of TBLA, this study aims to integrate the 4th grade language testing into language learning process through ILTPY (Integrated Language Testing Program for Young Learners). ILTPY includes ten-unit assessment tasks which have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Using Tayeb et al (2018), Sarigoz and Fişne (2019), Liu and Ren (2021), and Prianty et al (2021), study results in which all of them explored the washback effect of TBA, the present paper aimed to provide further evidence on the washback effect of TBA of vocabulary on EFL learners. The study of Sarigoz and Fişne (2019) revealed by utilizing an integrated language testing program that included 10-unit assessment tasks, TBA significantly increased the level of language learning in the 4th grade. The result of this study agreed with the results of Prianty et al (2021), since considerable similarities existed between these two.…”
Section: International Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Tayeb et al (2018), Sarigoz and Fişne (2019), Liu and Ren (2021), and Prianty et al (2021), study results in which all of them explored the washback effect of TBA, the present paper aimed to provide further evidence on the washback effect of TBA of vocabulary on EFL learners. The study of Sarigoz and Fişne (2019) revealed by utilizing an integrated language testing program that included 10-unit assessment tasks, TBA significantly increased the level of language learning in the 4th grade. The result of this study agreed with the results of Prianty et al (2021), since considerable similarities existed between these two.…”
Section: International Studiesmentioning
confidence: 99%
“…In the second study, teachers' perceptions of TBLT, including TBA were explored and the results demonstrated teachers' positive attitudes toward the utilization of TBLT, even though most of them had little knowledge about TBLT and assessment. In the first study, Sarigoz and Fişne (2019) stated that both teachers and learners were satisfied with integrating TBLA into the classroom setting. The results of both studies confirmed the reality that traditional types of assessment fail to satisfy the students and teachers.…”
Section: International Studiesmentioning
confidence: 99%